2018
DOI: 10.4236/ampc.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

Microprobe Mapping of Rare Earth Element Distribution in Round Top Yttrofluorite Deposit

Abstract: The electron microprobe maps the spatial distribution of elements in a rock at a sub-mineral-grain scale to provide a basis for understanding mineralization processes and to determine optimal strategies for extraction of valuable target elements. Round Top Mountain (near the town of Sierra Blanca, Hudspeth County, west Texas, USA) is a peraluminous rhyolite laccolith that is homogeneously mineralized at over 500 ppm rare earths, more than 70% of which are yttrium and heavy rare earths (YHREEs). The massive dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The significance of the even distributions of U and Nb, and other minor and trace elements not included here, is that they confirm the well-mixed nature of the rhyolite laccolith [20] [21] [31] [32] [33]. Thus an even grade is not just an oddity of the REEs, but reflects the well-mixed nature of the deposit itself.…”
Section: Grades Of Other Elementsmentioning
confidence: 86%
“…The significance of the even distributions of U and Nb, and other minor and trace elements not included here, is that they confirm the well-mixed nature of the rhyolite laccolith [20] [21] [31] [32] [33]. Thus an even grade is not just an oddity of the REEs, but reflects the well-mixed nature of the deposit itself.…”
Section: Grades Of Other Elementsmentioning
confidence: 86%
“…The previous study [9] defined the mineral deposits and confirmed the potential resource but they did not provide definitive information on how to extract the desired minerals efficiently and economically. For that reason, we conducted further analyses, including more experimental techniques, to better understand a basis for recovering the HREEs at Round Top Mountain economically.…”
Section: Introductionmentioning
confidence: 92%
“…Polished thin sections underwent an ultrasonic cleaning bath, an ethanol rinse, and carbon coating prior to analysis. Thin section preparation procedure followed [9].…”
Section: Thin Section Preparationmentioning
confidence: 99%
See 2 more Smart Citations